Materiality and intentionality. Some difficulties of material agency theory and the ecological approach - Vaccari, Andrés Pablo; Parente, Diego (Estudios de Filosofía, 2017)
In this paper we evaluate the strengths and limitations of two approaches that privilege material dimensions of technology in their respective accounts of technical practice: the ecological account of Tim Ingold and the material agency theory of Lambros Malafouris. Both these authors eschew the centralized intentionality of classical approaches in favor of epistemic externalism: the view that ecological and material affordances are the key drivers of agency in action, and determinant of artifactual form. We argue that these approaches have significant difficulties accounting for some amply recognized, key features of technical agency at the center of debates in the philosophy of technology—namely, its normative and teleological aspects.